Transnational Performance, Identity and Mobility in Asia (Springer Singapore, 2018)
This pivot considers the history, methodology and practice of Asian theatre and investigates the role of Asian theatre and film in contemporary transnational Asian identities. It critically reviews the topics of transnationalism and intercultural political difference, arguing that the concept of Transnational Asian theatre or 'TransAsia' acan promote cultural diversity and social transformation. The book notably offers an understanding of theatre as a cultural laboratory, a repository for diverse histories and a forum for intercultural dialogue, allowing for a better understanding of sociocultural patterns surrounding transnational Asian identity and mobility.